2016
DOI: 10.1002/2015jb012382
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic rotation pattern of the southern Chile fore‐arc sliver (38°S–42°S): A new tool to evaluate plate locking along subduction zones

Abstract: The Chile fore arc at 37°S–47°S represents the coseismic deformation zone of the 1960 Mw 9.5 Valdivia earthquake. Here we report on the paleomagnetism of 43 Oligocene‐Pleistocene volcanic sites from the fore‐arc sliver between 38°S and 42°S. Sites were gathered west of the 1000 km long Liquiñe‐Ofqui dextral fault zone (LOFZ) that represents the eastern fore‐arc sliver boundary. Nineteen reliable sites reveal that the fore arc is characterized by counterclockwise (CCW) rotations of variable magnitude, except at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 125 publications
1
27
1
Order By: Relevance
“…The highly rotated sites from the Lanping domain edges suggest that strike‐slip deformation along the ARRSZ and Chongshan shear zones (constrained mainly at 32–15 Ma) resulted in the rotation of small kilometer size blocks up to a distance of at least 12 km from the shear zone (Figure ). Such strike‐slip‐related crustal block rotations have been widely documented elsewhere (e.g., Beck, ; Hernandez‐Moreno et al, , ; Kimura et al, , ; Piper et al, ; Randall et al, ; Ron et al, ). Within north Indochina, Pellegrino et al () showed that crust east of the Gaoligong shear zone was broken in ≥1 km wide crustal blocks that experienced CW rotations of about 180° and that rotations ended at a ~20 km distance from the shear zone.…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingmentioning
confidence: 66%
“…The highly rotated sites from the Lanping domain edges suggest that strike‐slip deformation along the ARRSZ and Chongshan shear zones (constrained mainly at 32–15 Ma) resulted in the rotation of small kilometer size blocks up to a distance of at least 12 km from the shear zone (Figure ). Such strike‐slip‐related crustal block rotations have been widely documented elsewhere (e.g., Beck, ; Hernandez‐Moreno et al, , ; Kimura et al, , ; Piper et al, ; Randall et al, ; Ron et al, ). Within north Indochina, Pellegrino et al () showed that crust east of the Gaoligong shear zone was broken in ≥1 km wide crustal blocks that experienced CW rotations of about 180° and that rotations ended at a ~20 km distance from the shear zone.…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingmentioning
confidence: 66%
“…The described CW paleomagnetic data seem to support a “quasi‐continuous” crust deformation model of strike‐slip fault zones, where the upper brittle crust is broken into small rigid blocks with sizes smaller than the shear zone width, the rotation is CW (CCW) in regions of dextral (sinistral) shear and gradually increases getting closer to the fault, reaching values >90° (Figure c; Hernandez‐Moreno et al, , ; McKenzie & Jackson, ; Nelson & Jones, ; Randall, Lamb, & Mac Niocaill, ; Sonder et al, ).…”
Section: Rotation Pattern Along the Gaoligong Shear Zonementioning
confidence: 62%
“…To the west of the fault, Pliocene‐Holocene basalts overall show null rotations, consistently with results from the Pliocene whitish silt site Yun07. As discussed above, PSV from basalt sites is likely not averaged out, and we may expect a geomagnetic declination scatter that mostly ranges within ±20° at such latitudes (Hernandez‐Moreno et al, , and discussion therein). Thus, a bias can exist on the average null rotation obtained from volcanic data, but such error is expected to be much smaller than the large CW rotations (up to 176°) observed in Mesozoic red beds.…”
Section: Rotation Pattern Along the Gaoligong Shear Zonementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, strike‐slip faults yield rotations that peak at maximum values along fault trace and decrease—progressively or stepwise—moving away from it (Kimura et al, ; Sonder et al, ). The width of the rotation zone straddling the fault varies from hundreds of meters to few tens of kilometers and is a function of fault length, total displacement, locking of the fault zone, and crust rheology (Hernandez‐Moreno et al, , ; Kimura et al, ; Lamb, ; McKenzie & Jackson, ; Randall et al, ; Sonder et al, ).…”
Section: Introductionmentioning
confidence: 99%